ASSESSMENT OF THE EFFECTIVENESS OF MARKETING ACTIVITIES IN A DEVELOPMENT COMPANY: APPROACHES AND TOOLS - Fisunenko, Pavlo; Ignatenko, Oleksandr (Current Problems of Sustainable Development, 2026)
The article examines modern approaches and tools for assessing the effectiveness of marketing activities in development companies in the real estate market. The authors emphasize the specifics of the development industry, in particular the long sales cycle, the high cost of objects and the significant dependence of results on external economic and regulatory factors, which complicates the standard measurement of the effectiveness of marketing activities. The article examines the main approaches and tools for assessing the effectiveness of marketing activities in development companies. The emphasis is on the specifics of the real estate market, which requires a comprehensive approach to analyzing the results of marketing activities. The paper proposes a comprehensive approach to assessment that combines quantitative indicators (sales volume, return on investment in marketing, cost of attracting customers) and qualitative criteria (level of customer satisfaction, brand recognition, audience loyalty). The use of various tools is considered: CRM systems for collecting and analyzing data on potential buyers, digital analytics for monitoring the effectiveness of advertising channels, as well as financial analysis methods for comparing marketing costs with income received. Special attention is paid to the need for regular auditing of marketing activities and adaptation of strategies based on the results obtained. The proposed methodology can be used by development companies to increase the effectiveness of their marketing strategies, optimize budgets and strengthen competitive positions in the real estate market. The material of the article is of practical importance for marketers, sales managers, as well as researchers working in the field of real estate. Marketing activities are one of the key factors of success of development companies in the modern real estate market. The highly competitive environment requires a deep understanding of the results of marketing activities and their impact on key business indicators. Evaluating the effectiveness of marketing activities allows not only to track the success of campaigns, but also to adjust strategies to ensure long-term business development. The purpose of this article is to analyze the main approaches to assessing the effectiveness of marketing activities in development companies, as well as to consider the most effective tools for conducting such an assessment.
Keywords: marketing activities; effectiveness; performance; evaluation; development company; real estate market; evaluation tools; customer experience; marketing analysis; strategy; innovation